2018
DOI: 10.1080/02640414.2018.1466493
|View full text |Cite
|
Sign up to set email alerts
|

Clustering performances in the NBA according to players’ anthropometric attributes and playing experience

Abstract: The aim of this study was: (i) to group basketball players into similar clusters based on a combination of anthropometric characteristics and playing experience; and (ii) explore the distribution of players (included starters and non-starters) from different levels of teams within the obtained clusters. The game-related statistics from 699 regular season balanced games were analyzed using a two-step cluster model and a discriminant analysis. The clustering process allowed identifying five different player prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 48 publications
(51 reference statements)
1
60
0
2
Order By: Relevance
“…Although we did not find any differences regarding the players' specific position, it might be arguable that individual physical characteristics may influence their improvements. Particularly in team sports like basketball, players have well-defined roles that requires specific and distinctive physical attributes [32,33,56]; hence, a different response to BJ supplementation can be expected. In this sense, it can be arguable that athletic and explosive players (e.g., guards or forwards) would have greater benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find any differences regarding the players' specific position, it might be arguable that individual physical characteristics may influence their improvements. Particularly in team sports like basketball, players have well-defined roles that requires specific and distinctive physical attributes [32,33,56]; hence, a different response to BJ supplementation can be expected. In this sense, it can be arguable that athletic and explosive players (e.g., guards or forwards) would have greater benefits.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most determining factors in sports performance is the tactical technical analysis of the competition (Cui et al, 2018; Zhang et al, 2018). This type of analysis allows coaches to obtain information about the performance indicators, apart from knowing the weaknesses and strengths from their own and the adversaries, offering the possibility of improving training processes and therefore, increasing the possibilities of performance and success possibilities from the players (O'Donoghue and Ingram, 2001; Sainz De Baranda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was observed that the sports potential evaluated by coaches privileges athletes with larger body size and biologically more advanced. The sports potential classification of young athletes through multivariate techniques, such as cluster analysis, has aroused the interest of several researchers [14][15][16][17][18] . The use of multivariate statistical techniques allows the establishment of non-linear relationships between the various evaluations, presenting better capacity for the generalization of results, increasing the quality of the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…There is scientific evidence that the results obtained in test batteries for young athletes are able to predict sport success. Young people with above-average performance in tests tend to be the most successful in the future 16 and diagnosis using test batteries has shown greater prognostic capacity compared to coach's opinion 30 . In Switzerland, for example, a recent longitudinal study with young soccer players aged 12-15 years found that the most promising ones are not necessarily the best, but rather those who present above-average performance in physicomotor and skill tests consistently over the years, with emphasis on a holistic perspective in the selection of talents, that is, person-oriented 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation